El índice z en la condición física para la detección y selección de talentos deportivos - Pazmiño Calero, José Oswaldo (2019)
We investigated a method of sports selection for the detection of the innate talent of the individual with characteristics superior to the means of communication of the normal population. The objective was to evaluate and select through the index. Physical fitness and anthropometric values of children and adolescents. The sample consisted of 314 subjects with ages between 12 and 14 years, the application of the statistical method of the index. Above the average of the population. The size of the sample shows an average height of 154.96 ± 8.314 cm. The speed in 30 meters thrown has an average of 5.58 ± 0.783 seconds of difference. The arm extension flexo shows an average of 6.74 ± 5.496 repetitions. The abdominal strength averaged 14.67 repetitions and a deviation of 5,019 repetitions. The long jump has an average of 139.01 and the standard deviation of 23.45. The resistance test in 1000 meters presents an average of 4.57 minutes, with a standard deviation of 2.35 minutes. We observed 2 female subjects who recorded 4 deviations from the media of the population being these in strength of arms and abdominal strength, while in the male population there are 2 individuals who register males over 4 deviations in the speed test, one in the strength of arms and 1 in the abdominal strength